Results of the Feasibility of Material and Media Aspects of Teaching Books on Sports Nutrition - Lufthansa, Luthfie; Rusdiawan, Afif; Yahya, Alfian; Pawitra, Paulus Rah Adi; Sari, Reno Siska (Universitas Malikussaleh, 2019)
This study aims to determine the results of the feasibility of the material aspects and media of sports nutrition teaching textbooks. This research is a research on the development of sports nutrition science textbooks. The development of the teaching book on Nutrition Sports Science refers to the 4D model developed by Thiagarajan, et al. (1974) which consists of 4 stages, namely Define, Design, Development, and Disseminate, modified to be adapted to this study. This textbook is tested by material and media experts. The instrument used is an expert validation instrument. Based on the results of the study it can be concluded that the Sports Nutrition Science textbook was declared fit for use as a sports Nutrition Science textbook by material and media experts.